State of development of sport and technical and applied sports in the sports organizations of Ukraine - Tikhonova, N.V.; Gradusov, V.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : the study of the development of sport and technical and applied sports in the sports organizations of Ukraine. Material : the results of analysis of scientific and methodical literature, statistical reports of the Ministry of Youth and Sports, controls for Physical Culture and Sport, the governing bodies of education and science, society websites promoting Defence of Ukraine, the Sports Committee of Ukraine. Results : technical sports solve complex health and educational problems, promote patriotic education of children. In Ukraine today gaining popularity of sports-technical and applied sports. According to statistics the number of students enrolled in 2013 increased by 6% (1720 people) in relation to 2012. Total 30484 person. The most popular among children and adolescents are: military-sport all-around (amount involved is 23.9% of the total number of pupils), fire-applied sports (8.8%), parachute (8.7%), automotive (8.1 %), model aircraft (7.8%), underwater (5.8%), radio sport (7.1%). The most abundant component in the number of sports clubs have engaged in occupations which covered 18264 children and adolescents. Conclusions : Implementation of measures for further development of sports engineering, aviation and military applied sports will foster a versatile development, hardened physically, technically trained people. As the formation of the younger generation of sustained interest and needs in the classroom technical creativity, provide training for young people for military service and active labor.